2016
DOI: 10.1002/bjs.9966
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial to examine procedure-to-procedure transfer in laparoscopic simulator training

Abstract: NCT02069951 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
(43 reference statements)
1
18
0
1
Order By: Relevance
“…1 Thus, surgical trainees must acquire the skills and level of proficiency in laparoscopic surgery. 2 Setbacks and health policies safeguarding patient safety threaten and limit the exposure of surgical trainees to laparoscopic surgery. [3][4][5][6][7] To tackle this problem, surgical training centres provide opportunities through simulation and virtual reality.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thus, surgical trainees must acquire the skills and level of proficiency in laparoscopic surgery. 2 Setbacks and health policies safeguarding patient safety threaten and limit the exposure of surgical trainees to laparoscopic surgery. [3][4][5][6][7] To tackle this problem, surgical training centres provide opportunities through simulation and virtual reality.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in another area of orthopaedics, Dubrowski et al 12 suggested that practicing the entire task of bone plating yielded more learning than practicing isolated individual skills. In other surgical fields, Bjerrum et al 4 found little transfer of skills from one laparoscopic procedure to another, while Thomsen et al 31 found no evidence of transfer from one intraocular surgical procedure to another.…”
Section: Discussionmentioning
confidence: 99%
“…Procedure‐to‐procedure transfer has not been previously investigated for entire ophthalmic procedures, and notably, in laparoscopic surgery, results are inconsistent (Bjerrum et al. ). Basic skills training using instruments similar to real life (black‐box training) has shown to prepare trainees for thoracoscopic lobectomy more effectively than advanced high‐fidelity simulation training in nephrectomy (Jensen et al.…”
Section: Discussionmentioning
confidence: 99%